Investigation of the Effect of Grain Size and Wire Size on the Mechanical and Structural Properties of Polycrystalline Ni Nano Wire Using Molecular Dynamics Simulation - Kazanç, Sefa; Canbay, Canan Aksu (My University, 2025)
The effect of grain size and length-to-diameter ratio (LDR) on the mechanical properties of polycrystalline Ni nanowire was examined by molecular dynamics simulation as a result of uniaxial tensile deformation applied at a temperature of 300 K. The Embedded Atom Method (EAM) was used to determine the forces acting on the nanowire atoms. Elastic modulus (E), yield strength and fracture stress values were determined from the stress-strain relationship determined as a result of the deformation process. Microstructural changes resulting from plastic deformation were examined from the atomic positions determined using the common neighbor analysis method (CNA). It was determined that grain size and LDR had a significant effect on the deformation behavior of Ni nanowire, and plastic deformation and breaks resulted from the rearrangement of atomic positions by surface effect and also the nanowires with small grain size and LDR exhibited superplasticity behavior. The grain size in the modeled polycrystalline nanowire system affected the movement mechanisms of the grains, grain boundaries, and the relationship between grain size and flow force was investigated. From this relationship, the Hall-Petch effect and the reverse Hall-Petch effect were observed after a certain critical grain size.
Keywords: Molecular dynamics; nanowire; Hall-Petch effect; Polycrystal; superplastic